Evaluating living standard indicators - Nad'a Birciaková; Jana Stávkova; Veronika Antosová (DANUBE: Law, Economics and Social Issues Review, 2015)
This paper deals with the evaluation of selected available indicators of living standards, divided into three groups, namely economic, environmental, and social. We have selected six countries of the European Union for analysis: Bulgaria, the Czech Republic, Hungary, Luxembourg, France, and Great Britain. The aim of this paper is to evaluate indicators measuring living standards and suggest the most important factors which should be included in the final measurement. We have tried to determine what factors influence each indicator and what factors affect living standards. We have chosen regression analysis as our main method. From the study of factors, we can deduce their impact on living standards, and thus the value of indicators of living standards. Indicators with a high degree of reliability include the following factors: size and density of population, health care and spending on education. Emissions of carbon dioxide in the atmosphere also have a certain lower degree of reliability.
Keywords: 330; Living Standards; Indicators; Quality of Life; Well-being; European Union